2006
DOI: 10.1007/bf02985595
|View full text |Cite
|
Sign up to set email alerts
|

An abnormal accumulation of fluorine-18-FDG PET in cytomegalovirus enteritis—A case report

Abstract: The source of a fever of unknown origin (FUO) and watery diarrhea in a 63-yr-old female with a history of disturbance of consciousness due to moyamoya disease was examined. Fluorine-18 fluorodeoxyglucose positron emission tomography (FDG-PET), colonoscopy, blood analysis, and determination of cytomegalovirus (CMV) antigenemia were performed. FDG was found to be accumulated in the wall of a dilated colon, and extended from the transverse to sigmoid colon. Colonoscopy revealed edematous, inflammatory, and punche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…CMV infections can show increased FDG uptake in PET scans. For example, lymphadenitis [ 20 ], GI infections [ 27 , 28 ], and infectious mononucleosis [ 29 ]. A case of CMV lymphadenitis mimicking lymphoma relapse in PET scan has been reported [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…CMV infections can show increased FDG uptake in PET scans. For example, lymphadenitis [ 20 ], GI infections [ 27 , 28 ], and infectious mononucleosis [ 29 ]. A case of CMV lymphadenitis mimicking lymphoma relapse in PET scan has been reported [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The changes revealed by the PET/CT were consistent with an acute infectious colitis. Only one case of 18 F-FDG uptake in acute CMV colitis has been previously reported [8]. This case highlights that a positive 18 F-FDG PET/CT scan of the colon can be due to CMV colitis.…”
mentioning
confidence: 71%
“…It has been reported that abnormal FDG accumulation is occasionally observed in infection by CMV or Epstein-Barr virus [5][6][7]. Also, clonal T-cell expansion is also observed in CMV infection [8,9].…”
Section: Discussionmentioning
confidence: 99%